Infecção por Aeromonas hydrophila em jundiá: estresse e efeito terapêutico da combinação de florfenicol com linalol via banho - Bandeira Junior, Guerino (2022)
The first article consisted of a review article whose objective was to synthesize the current knowledge regarding the effects of aeromonosis on fish oxidative status. The second article consisted of an original article whose objective was to evaluate the effect of Aeromonas hydrophila infection on individual behavior (novel tank test) and brain expression of stress-related genes (slc6a2, hsp90, hspa12a, hsd20b, hsd11b2, crh) in silver catfish (Rhamdia quelen). The third article consisted of an original article whose objective was to evaluate the effect of the combination of florfenicol with linalool via bath against aeromonosis in silver catfish and their responses in the redox balance and histology of gills, liver and caudal kidney. Regarding the review article, we can conclude that increased levels of reactive oxygen species (ROS), malondialdehyde (MDA) and protein carbonylation (PC) indicate that Aeromonas infection generally causes oxidative stress. Therefore, these three biomarkers are excellent indicators of oxidative stress during infection. In addition, the increase in respiratory burst activity (RBA) and nitric oxide (NO) levels indicate that the fish's innate immune system is generally more active during infection. Regarding the second article, we can conclude that A. hydrophila infection in silver catfish causes stress-related hyperlocomotion and changes in the hypothalamic-pituitary-interrenal (HPI) axis, increasing the cerebral expression of hspa12a and crh, which are related to heat shock protein and cortisol synthesis route, respectively. Finally, regarding the third article, we can conclude that the combined use of florfenicol with linalool via bath had a beneficial effect on the levels of thiobarbituric acid reactive substances (TBARS) and histopathological analyzes in gills and liver of silver catfish experimentally infected with A. hydrophila. Despite the considerable loss by evaporation, a satisfactory linalool concentration remained one day after the bath.